Inducing Apoptosis and Suppressing Inflammatory Reactions in Synovial Fibroblasts are Two Important Ways for Guizhi-Shaoyao-Zhimu Decoction Against Rheumatoid Arthritis - Zhang Q (Dove Medical Press, 2021)
Qing Zhang,1 Hu-Xinyue Duan,1 Ruo-Lan Li,1 Jia-Yi Sun,2 Jia Liu,1 Wei Peng,1 Chun-Jie Wu,1 Yong-Xiang Gao3 1School of Pharmacy, Chengdu University of Traditional Chinese Medicine, Chengdu 611130, People’s Republic of China; 2Innovation Research Institute, Chengdu University of Traditional Chinese Medicine, Chengdu 610075, People’s Republic of China; 3School of Basic Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu 610075, People’s Republic of ChinaCorrespondence: Chun-Jie WuSchool of Pharmacy, Chengdu University of Traditional Chinese Medicine, Chengdu 611137, People’s Republic of ChinaTel +86-28-61801001Email wucjcdtcm@163.comYong-Xiang GaoSchool of Basic Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu 610075, People’s Republic of ChinaTel +86-28-61801001Email gaoyxcdtcm@126.comBackground and Objectives: Guizhi-Shaoyao-Zhimu decoction (GSZD) is often applied to control rheumatoid arthritis (RA), gout, osteoarthritis, etc. In this study, bioinformatic analysis and experimental verification were used to uncover the integral mechanism profile of GSZD against RA.Materials and Methods: The chemical compositions of GSZD were identified by UPLC-QTOF-MS/MS. MH7A cell model was established to screen active compounds in GSZD, and potential targets of these compounds were predicted through online database retrieval. The differential expression genes (DEGs) in synovial tissue of RA patients and normal controls were retrieved from the GEO database. DEGs and the predicated compounds targets were overlapped, and the overlapped genes were subsequently enriched by GO and KEGG analysis. The pathways with significant enrichments were further experimentally verified.Results: A total of 19 constituents were identified from GSZD, and 11 compounds showed obviously antiproliferative effects on MH7A cells with IC50 < 100 μg/mL. Bioinformatic analysis indicated that IL-1β, IL-6, MAPK8, JAK2, CXCL8, and CASP3 were the main targets of GSZD, and the integral pharmacological mechanisms profile of GSZD might be related to anti-inflammation and proapoptosis. GSZD can promote the loss of mitochondrial membrane potential (MOMP) and induce apoptosis in MH7A cells. Furthermore, in vitro experiments showed GSZD can not only downregulate mRNA expressions of IL-1β (p< 0.05), IL-6 (p< 0.05), MMPs (p< 0.05) and CCL5 (p< 0.05) but also inhibit the nuclear transcription of NF-κB. GSZD also reduced the expressions of Bcl-2 (p< 0.05), JAK2 (p< 0.05), STAT-3 (p< 0.05), whereas increase Bax (p< 0.05), Caspase-3 (p< 0.05) and caspase-9 (p< 0.05).Conclusion: Collectively, inducing synovial fibroblast apoptosis and inhibiting inflammatory response are two important ways for GSZD to RA, and our study proved bioinformatic analysis combined with experimental verification is a feasible method to explore the drug targets and mechanism of actions of TCMs.Keywords: apoptosis, anti-inflammatory, bioinformatic analysis, rheumatoid arthritis, Guizhi-Shaoyao-Zhimu decoction